Revolutionizing Environmental Accountability through Corporate Practices: Merevolusi Akuntabilitas Lingkungan melalui Praktik Perusahaan - Puspanegara, Amelia; Widodo, Heri (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the application of environmental accounting as a strategy for addressing environmental impacts and enhancing corporate social responsibility (CSR) at CV. Royal Super Feed. Despite providing local employment, the company faces challenges such as industrial waste pollution impacting the surrounding community and ecosystem. Through qualitative methods including observations, interviews, and documentation analysis, the research examines environmental accounting practices and corporate policies aimed at mitigating environmental damage and promoting sustainability. Findings highlight significant environmental costs related to waste management and CSR programs focused on community welfare and environmental development. The study underscores the importance of environmental accounting in monitoring resource use, assessing impacts, and fostering sustainable business practices, offering insights for companies aiming to integrate environmental concerns into their operational frameworks effectively. Highlights: Tracks resource use, assesses impacts. Enhances community welfare, environmental development. Insights from observations, interviews aid understanding. Keywords: Environmental accounting, CSR, industrial waste pollution, sustainability, qualitative research